(untitled) (Journal of Educational Sciences, 2019)
This article discusses the developed methodology for the adaptation of children with mental retardation in the context of inclusive education. The study involved 20 children with mental retardation, students in inclusive classes of secondary schools, as well as parents of these children. The experimental work carried out in three stages: at the first stage, a complex of organizational and pedagogical conditions developed for the adaptation of children with delayed psychical development by means of inclusive education in an educational institution. The second diagnostic and staging stage there was a theoretical and pedagogical justification; teaching and methodological, didactic and advisory materials created for parents and teachers. A stating experiment conducted; at the third stage, the organization of experimental work in general education schools on the implementation of a set of organizational and pedagogical conditions for the adaptation of children with delayed psychical development by means of inclusive education (formative experiment). According to the results of the formative experiment, it found out that inclusive education makes it possible to ensure the socialization of children in this category; each child can develop in his or her own way and receive affordable quality education tailored to their individual needs and their own opportunities in an inclusive education environment. Key words: children with delayed psychical development, inclusive education, attention, thinking, teacher-defectologist, psychologist.